Born in Belo Horizonte: the trajectory of parturient women and their reproductive outcomes - Torcata Amorim; Mariana Santos Felisbino-Mendes; Rafaela Siqueira Costa Schreck; Sabrina Paiva Ribeiro; Edna Maria Rezende; Eunice Francisca Martins
ABSTRACT Objective: To analyze the trajectory taken by pregnant women for delivery care in Belo Horizonte and its relation with the reproductive outcomes. Method: A cross-sectional study using a database from a study conducted in Belo Horizonte. The studied variables were referent to the trajectory of women seeking delivery care, to their social, demographic and health care characteristics, and to the reproductive outcomes. Odds Ratios were estimated with their 95% confidence intervals to evaluate the factors associated with unfavorable trajectory and outcomes. Results: A total of 1,087 cases were studied, of which 39.3% had an unfavorable trajectory. The chance of having an unfavorable trajectory was higher for women who were not Belo Horizonte residents, with lower education, non-white race/color, and who had undergone prenatal care in public healthcare service. The prevalence of reproductive outcomes was similar regardless of the trajectory status, except for vaginal delivery. Conclusion: An unfavorable trajectory remains high, and shows weaknesses in the health care services network to guarantee timely and qualified access to pregnant women. However, the care received in the health services outweighs the risks of an unfavorable trajectory.